Effect of RF carbonitriding and improvement of mechanical properties on AISI 304 stainless steel – A review. (2020) - Vaijayanth, Sheri; Koppula, Shivani; Sateesh, N.; Subbiah, Ram
Abstract: The examination is made on RF plasma carbonitriding of AISI-304 austenitic hardened steel and enrolled the outcomes as an element of plasma time and distinctive plasma powers (300–650 W). The surface hardness of the regarded surfaces just as the microhardness profile of the examples was estimated. For the example treated for 10 min, the pace of carbonitriding was determined to be ∼0.5 μm 2 /s. The surface hardness of the carbonitrided layer prepared for 10 min was 1715 Hv, 0.1 when contrasted with 228 Hv, 0.1 for the untreated surface. The high pace of carbonitriding (1 μm 2 /s) and 2 the high hardness of CNASS (1375 Hv, 0.1) at plasma input power 550 W have been deciphered as far as nitrogen and carbon fixation inclinations, and microcracks framed in the surface during the plasma procedure in the compound layer.